Strategic Organizing and Workforces Performance of Iraqi Oil Companies - Al-Frijawy, Jawad (South Asian Journal of Social Sciences and Humanities, 2022)
Strategic organizing is an organizational management activity that must be effective and measurable implemented in the company to achieve the desired results. The organization as a well implemented strategic plan to manage the external changes. The aim of the research is to reveal the extent of the impact of strategic organizing on the performance of workforces in Iraqi oil companies. The research was conducted in Basra Oil Company as a field of study. The researcher adopted a major hypothesis that (there is a statistically significant impact of strategic organizing and its variables on the performance workforces of Iraqi oil companies. Sample of (145 people) was selected, and the questionnaire was used as a tool for data collection. The result the most important of which is (the Iraqi oil companies need to work according to the concepts and requirements of strategic organizing ).
Keywords: Strategic organizing; Workforces Performance; Oil Companies.